STRENGTHENING OF PUBLIC-ADMINISTRATION’S PROBLEM IN THE ENVIRONMENTAL FIELD: WORLD AND UKRAINIAN REALITIES - Holynska , Olesya; Bieloshapka , Tetyana (Pressing Problems of Public Administration, 2021)
Preserving the environment and finding an effective environmental policy is the most acute problem of mankind. The article analyzes the literature revealing the importance of public administration in the field of environmental protection. The legislative framework and the works of scientists, where the questions of the current state of public administration in the field of environmental protection were investigated. The important directions concerning the necessity of ecologization of public administration in our time, both at the regional and the local level, are highlighted. The emphasis is placed on the urgency of forming the ecological consciousness of society as a prerequisite for the further sustainable development of the state as a whole. The role of society and the technogenic loading, ecological programs and existing normative-legal acts in the creation of a new environmental policy of the local level is being studied. As the experience of developed countries shows, it is difficult to pursue an effective environmental policy in a country, even in a prosperous economy based on this state. The greening of the public administration system is a sign of its realities, and, according to leading scholars, it has a steady trend of deepening in order to change the main subject-object relations and influences in the mechanisms of public administration of modern times. A number of conclusions that are problematic and are subject to further scientific discussion to identify opportunities for the development of organizational and economic mechanism of public administration in modern conditions of state.